zapisz wyrażenia nie używając nawiasów a następnie zredukuj wyrazy podobne.
przykład:
(4x - 7) - (3x - y) = 4x - 7 - 3x + y = x + y - 7

a) 8a +(4a - 7)=
b)5a- (3a + 6)=
c) -8 m + (2n - m )=
d) -3p -(6r - 4p)=
e) 2x - 7y + (5x - 2 y ) =
f) -2 + 8y - (6x - 7y)=
g) (3u - 6v ) + 6v -5) =
h) (8u + 3v) - (2u+ 5v) =
i) (-a - 4b) + (5b- a)=
j) (7a -b ) - (4a - 2b)=


Odpowiedź :

a) 8a+4a-7 =12a-7
b) 5a-(3a+6)= 5a-3a-6=2a-6
c) -8m+2n-m= -9m+2n
d) -3p-6r+4p= p-6r
e) 2x-7y +5x-2y= 7x-9y
f) -2x+8y-6x+7y= -8x+15y
g) 3u-6v+6v-5=3u-5
h) 8u+3v-2u-5v=6u-2v
i) -a-4b+5b-a= -2a+b
j) 7a-b-4a+2b= 3a+b

Viz Inne Pytanie